2015
DOI: 10.5935/abc.20150001
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Blood Pressure and Cardiovascular Outcomes in Hypertensive Patients in a Reference Center

Abstract: BackgroundHypertension is a public health problem, considering its high prevalence, low control rate and cardiovascular complications.ObjectiveEvaluate the control of blood pressure (BP) and cardiovascular outcomes in patients enrolled at the Reference Center for Hypertension and Diabetes, located in a medium-sized city in the Midwest Region of Brazil.MethodsPopulation-based study comparing patients enrolled in the service at the time of their admission and after an average follow-up of five years. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
3
6
0
3
Order By: Relevance
“…The low control rate found in our study is consistent with other recent studies, including one conducted in 2012 at a primary health care center in Rio Grande do Sul, in which 55.2% of the patients had controlled hypertension assessed by 24-hour ABPM, 20 and another study conducted by Guimarães Filho et al 22 at a hypertension and diabetes referral center in Goiás, which found an even lower BP control rate (39.6%) when the BP was measured by a conventional method. These studies suggest that regardless of the method used for BP measurement, the main reason for low BP control rates is the relationship between patients and health care professionals, emphasizing a need for multidisciplinary teams to improve the service provided to hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…The low control rate found in our study is consistent with other recent studies, including one conducted in 2012 at a primary health care center in Rio Grande do Sul, in which 55.2% of the patients had controlled hypertension assessed by 24-hour ABPM, 20 and another study conducted by Guimarães Filho et al 22 at a hypertension and diabetes referral center in Goiás, which found an even lower BP control rate (39.6%) when the BP was measured by a conventional method. These studies suggest that regardless of the method used for BP measurement, the main reason for low BP control rates is the relationship between patients and health care professionals, emphasizing a need for multidisciplinary teams to improve the service provided to hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…As already mentioned, IR and increased waist circumference are accompanied by increased release of proinflammatory mediators, particularly in adipose tissue (AT), in the liver and in skeletal muscle. 17,34,35 Adipose tissue itself is also related to inflammation and it is a long time since it was still considered a mere means of storing triacylglycerides and it is now known to be an endocrine organ that produces a wide range of adipokines such as IL-6, adiponectin, leptin, plasminogen activator inhibitor-1 (PAI-1) and TNF-α. Imbalances in the production of the chemical mediators modifies several factors associated with cardiovascular diseases (energy balance, insulin sensitivity, arterial blood pressure, lipid metabolism, immunity and homeostasis), promoting the development of a low intensity inflammatory process, which gives rise to a local immunoresponse characterized by an increase in inflammatory biomarkers, such as CRP and oxidative chemical species.…”
Section: Metabolic Syndrome Adipose Tissue and Aspects Of Inflammationmentioning
confidence: 99%
“…C-reactive protein also acts to regulate production of nitric oxide in vascular endothelium and coordinates production and secretion of many proinflammatory cytokines by adipocytes. 6,20,31,35,52 Published data show that increases in the levels of fibrinogen, fibrin and products of fibrinogen degradation are related to formation and development of atheromatous plaques. Fibrinogen plays a fundamental role in formation and growth of atheromatous plaques and is also a precursor of mural thrombi.…”
mentioning
confidence: 99%
“…[9] Systemic arterial hypertension is described as "a multifactorial clinical condition characterized by high and sustained levels of arterial blood pressure" with high rate and low control [10] Research has shown a Brazilian and global SAH prevalence varying from 25.5% to 37.8%. [11][12][13] Studies using the DCM have been widely used around the world in search of evidence regarding the association between the occurrence of health alterations in workers and the high strain and/or passive work, working environment. The results found for the prediction of health risk in relation to cardiovascular alterations, and more specifically SAH, are conflicting.…”
Section: Introductionmentioning
confidence: 99%